Determinan Adaptasi Karir, Pedoman Mencegah Turn Over Bagi Pekerja dari Pendidikan Sarjana - Samsul Arifin; Rahayu Mardikaningsih; Ella Anastasya Sinambela (STIE Mandala Jember, 2022)
The economic crisis due to the Covid-19 pandemic has influenced companies to make difficult decisions for their survival. This study discusses career adaptability among new graduates. Career adaptation is important for recent graduates to maintain their interest in the workplace. Graduates must understand the job and job description in order for them to carry out the task. Sometimes this may be a difficult process for them to digest and can make themselves feel demotivated, as they struggle to understand the job, and if dissatisfaction occurs it can result in an intention to leave the job. This study used 77 respondents and analysis using SPSS, correlation and regression were used to determine the most influential factors on career adaptation, from job satisfaction, work environment, and training and development. The results obtained are known that the factors that influence the career adaptation of fresh graduates are influenced by the independent variables of job satisfaction, training and development and the work environment. Keywords: career adaptation, turnover, education.